Analisis Ketersediaan dan Kebutuhan Kedelai di Provinsi Sumatera Utara - Situmorang, Sudiwan; Kuswardani, Retna Astuti; Effendi, Ihsan (Universitas Medan Area, 2020)
Soybean availability in North Sumatra Province have to be considered, this is caused by soybean being the third most important food after rice and corn. This study aims to analyze the factors that influence the availability and needs of soybeans in North Sumatra. This study uses secondary data on the availability and needs of soybeans in North Sumatra from 2008-2017. Secondary data collected in this study came from related agencies such as the Central Statistics Agency, the North Sumatra Province Food Security Agency, the North Sumatra Province Agriculture Office and the Belawan Agricultural Quarantine Center. From this study it was found that the availability of soybeans in North Sumatra was influenced by harvested area, soybean production and soybean imports. Soybean needs in North Sumatra are influenced by population, consumption / per capita and soybean availability. Analysis of soybean availability and needs in North Sumatra experienced fluctuations in 2008-2017.Â Â